2019
DOI: 10.1111/odi.13100
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual determinants of dental pain in adolescents: Evidence from a national survey

Abstract: Objective To investigate the prevalence of dental pain among adolescent students and its association with individual, school and city variables, using a multilevel approach. Subjects and Methods Individual and school data were obtained from the National Adolescent School‐Based Health Survey (PeNSE) conducted in Brazil in 2015 in a sample of 34,776 students from 1,339 schools in the 27 Brazilian capital cities. Secondary data on socioeconomic, structural and health indicators of the cities were obtained from pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
1
21
1
1
Order By: Relevance
“…With regard to age, we observed that older children had higher experience of previous dental pain. 11,25 This is not surprising, since older children are more likely to have more untreated carious lesions in Mexico. 5 However, this trend did not hold when age and current dental pain were examined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to age, we observed that older children had higher experience of previous dental pain. 11,25 This is not surprising, since older children are more likely to have more untreated carious lesions in Mexico. 5 However, this trend did not hold when age and current dental pain were examined.…”
Section: Discussionmentioning
confidence: 98%
“…8,10 Among factors associated with dental pain in both developed and developing countries are demographic, socioeconomic, family, psychosocial and cultural issues, as well as oral health status. 11 Recommendations from both the World Health Organization and the International Dental Federation include amelioration of dental pain as a priority goal in the International Agenda for the Oral Health Promotion. 12 However, in Mexico there are few epidemiological studies about dental pain.…”
Section: Introductionmentioning
confidence: 99%
“…12 Adolescence is the period of development between the ages of 10 and 19 years, 13 during which important biological and psychosocial changes occur. 13,14,15 A high prevalence of dental caries, gingival bleeding, and tooth loss has been commonly found in adolescents. 14,16 Despite the existence of public policies that benefit this group, such as a fluoridated water supply and universal healthcare, there are few specific programs directed at the oral health of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Multilevel studies about dental pain are rare and focused on children 24,25 or adolescents. 15,26 There is a gap in the literature on dental pain in the adult population adopting a multilevel approach. Therefore, it is important to evaluate health outcomes using individual and contextual determinants.…”
Section: Introductionmentioning
confidence: 99%